Specyfika stosunku obligacyjnego składu z udziałem domu składowego: [Description of a storage agreement whose party is a warehouse] (Studia Prawnicze / The Legal Studies, 2007)
Badania wskazują, że początek kształtowania się domów składowych miał miejsce w XVII w. w Anglii, rzadziej wskazuje się Holandię. Dla Europy kontynentalnej szczególne znaczenie w tym zakresie miało prawodawstwo francuskie. Chodzi o dekret z dnia 21 marca 1848 r., zmieniony następnie przez ustawę z dnia 28 maja 1858 r. o negocjowaniu towarami złożonymi w magazynach publicznych, udoskonaloną przez dekret z dnia 12 marca 1859 r., ustawę z 23 maja 1863 r. oraz dekret urządzający z 31 sierpnia 1878 r., które stały się wzorem dla innych państw w procesie tworzenia prawa o domach składowych. Z kolei na ziemiach naszego państwa w momencie uzyskania przez Polskę niepodległości obowiązywało pięć systemów prawnych regulujących instytucję domów składowych. W byłym zaborze austriackim domy składowe funkcjonowały na podstawie ustawy z dnia 28 kwietnia 1889 r. o zakładaniu i prowadzeniu publicznych domów składowych i o dowodach składowych, które domy takie wystawiają. Na ziemiach byłego zaboru niemieckiego obowiązywały w tej materii przepisy art. 416-424 kodeksu handlowego niemieckiego z 10 maja 1897 r. Na ziemiach wchodzących w skład byłego Cesarstwa Rosyjskiego sytuacja była zróżnicowana. O ile w województwach wschodnich problematyka ta była normowana przez przepisy art. 766-845 ustawy handlowej rosyjskiej (tom XI cz. II Zbioru Praw), o tyle w Królestwie Kongresowym w ogóle nie istniały w tym przedmiocie żadne regulacje. Dodatkowo na obszarze Spiszu i Orawy obowiązywały przepisy art. 434-452 węgierskiej ustawy handlowej (Artykuł Ustaw XXXVII z 1875 r.).  The article relates to the institution of a warehouse, which was restored in Polish legał system by an Act of 16th November 2000 on the bonded warehouses and on the amendment of the Civil Codę, the Civil Procedurę Codę and other acts (hereinafter be referred to as “the warehouse act”). The term of “warehouser” (also: “warehouse operator”) means a person who is lawfully engaged in the business of storing goods and entitled to issue warehouse receipts and to sell the storing goods in public auction. In accordance with the provisions of the warehouse act it is possible to claim that the Polish legislator imposed an obligation upon warehouses to exercise three kinds of functions. Firstly, warehousers are entrepreneurs who provide services of professional goods storage. The existing warehouse operators make the tumover of commodities morę comfortable and cheaper because it is not necessary for single participants to invest into expensive storehouses. In majority of cases modem warehouses are eąuipped with needed technical machines and installations, which allow to sort, reload and weight goods. Secondly, the aim of the warehousers is to improve circulation of the commodities. Thirdly, warehouse operators introduce a new base of obtaining a credit. These aims can be achieved by warehousers because they are authorized to issue security, which is called the warehouse receipt. The warehouse receipt consists of two parts: the first one is a reverse which is a document of title and makes selling goods possible without the necessity to move them; the second part of the security is a warrant defined as the warehouse pledge receipt. It is the source of credit. Since a new kind of the warehousers appeared, there are two kinds of storage contracts in Polish legał system now. The first one is regulated mainly by Civil Codę and defines entering into a contract with ordinary warehouse contractors, which is not entitled to issue the security and sell the goods in public auction. Warehouser operating under the warehouse act is a party of the second kind of storage agreement. This contract is regulated first of all by the provisions placed into the warehouse act, which are lex specialis toward rules of Civil Codę. As there are serious differences between these types of contracts, the aim of the author is to prove that apart from the common storage agreement there is also a particular kind of storage contract in Polish law. Besides the author examines if the regulations of the warehouse act are adapted to the needs of modem professional legał transactions and correspond to the reąuirements of the contemporary society.